Pleiotropic effects of anti-thrombotic therapies: have direct oral anticoagulants any anti-inflammatory effect? - Anna Maria Gori; Eleonora Camilleri; Alessia Bertelli; Angela Rogolino; Francesca Cesari; Elena Lotti; Tommaso Capobianco; Walther Iannotti; Betti Giusti; Rossella Marcucci (Bleeding, Thrombosis and Vascular Biology, 2022)
Direct oral anticoagulants (DOACs) are currently recommended by European guidelines as the first line therapy for both stroke prevention in patients with atrial fibrillation (AF) and the prevention and the treatment of venous thromboembolism (VTE). Recently, it has been speculated that DOACs have anti-inflammatory capabilities in reducing the abnormal release of pro-inflammatory factors in addition to inhibiting the activation of factor X or factor II of the coagulation cascade. However, this hypothesis is based on limited pathophysiological data with small sample size, often on in vitro studies. Real-world, in vivo, and large clinical data are scarce. The aim of the present study was the evaluation of the possible anti-inflammatory and anti-proliferative effects of DOACs treatment in a cohort of patients affected by AF or VTE, by analyzing an extensive panel of cytokines and molecules involved in the process of vascular and tissue remodeling. Our data evidenced that DOACs treatment is associated with variations in systemic inflammation markers and in metalloproteinases. Further studies with larger number of patients are required to confirm these data.